Anthropometric characteristics of elite male junior rowers. Issue 3 (1st June 2000) - Bourgois, Jan; Claessens, Albrecht L; Vrijens, Jacques; Philippaerts, Renaat; Van Renterghem, Bart; Thomis, Martine; Janssens, Melissa; Loos, Ruth; Lefevre, Johan
Abstract : During the 1997 Fédération Internationale des Sociétés d'Aviron World Junior Rowing Championships, anthropometric data on 383 male junior rowers were assessed. With 430 participating athletes, the sample represented 89% of the population. In addition to age, 27 dimensions were measured: body mass, six heights or lengths, four breadths, 10 girths, and six skinfolds. The elite male junior rowers were tall (187.4 (5.8) cm; mean (SD)) and heavy (82.2 (7.4) kg), with larger length, breadth, and girth dimensions than a nationally representative sample of Belgian boys of the same chronological age. A rowing specific anthropometric profile chart with norms was constructed. The stature of the junior rowers is similar to that of adult heavyweight elite rowers, except that the junior rowers are lighter. Compared with non-finalists, finalists are heavier (but still lighter than the adult heavyweight elite rower) and taller, with greater length, breadth (except for the bicristal diameter), and girth dimensions.